A bibliographic note on the first checklist of vascular plants of Zomin (also Zaamin, formerly Guralash) Nature Reserve, Uzbekistan - Sennikov, Alexander N. (Phytotaxa, 2012)
A bibliographic review of the first checklist of Zomin (formerly Guralash) Nature Reserve is presented, and the nomenclatural novelties appearing in this checklist are re-assessed. Twelve new names were introduced in two editions of the checklist, of which six were new species and two were new varieties. This review brings to light the overlooked but validly published combinations Aster altaicus var. canescens (Asteraceae) and Eremostachys speciosa var. brevicaulis (Lamiaceae). The name Eremurus chloranthus (Asphodelaceae) is found validly published but Henningia chlorantha is not. The valid publication of Scutellaria glabrata (Lamiaceae) is discussed.